Efektivitas Penerapan Manajemen Risiko Pada PT. Indofood Sukses Makmur - Rahmadanis Rahmadanis; Rani Novita; Reka Zulihanifa Wati; Reni Mardiana (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The field of science called risk management discusses how an organization can apply various management approaches in a comprehensive and systematic way to describe various existing problems. An enterprise is protected against significant risks through the use of risk management. Risk management is very important because it can prepare a company to face situations that can cause losses. There are several risk categories that can be tolerated. Small hazards are usually ignored, while major hazards must be avoided with the right plan. This research uses qualitative methods. Qualitative research is an approach based on the philosophy of postpositivism, which studies the state of natural objects. This study uses a literature study method to analyze the data. The risks that occur at PT Indofood are the risk of the COVID-19 pandemic, food safety risk, risk of rising commodity and raw material prices, competition risk, global warming and climate change risk, sustainability risk, and cyber security risk. From the results and discussion above, it can be concluded that PT Indofood Tbk has been effective in implementing risk management in various existing divisions